2022
DOI: 10.1021/acsomega.1c05393
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Highly Coordinative Fused Heterocycles Targeting β-Hematin Crystallization

Abstract: The β-hematin formation is a unique process adopted by Plasmodium sp. to detoxify free heme and represents a validated target to design new effective antimalarials. Most of the β-hematin inhibitors are mainly based on 4-aminoquinolines, but the parasite has developed diverse defense mechanisms against this type of chemical system. Thus, the identification of other molecular chemical entities targeting the β-hematin formation pathway is highly needed to evade resistance mechanisms associated with 4-aminoquinoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…From a perspective, we think that the use of a high CT probe bearing a basic moiety in the D–A chain may also be a convenient platform for the recognition of other chemical events dependent on the acidity, such as (i) the acidity of metals (hard–soft acid–base properties), (ii) identification of halogen-bonded adducts, and (iii) recognition of a hydrogen-transfer process upon excitation, such as PCET mechanisms through selective disruption of the ICT mechanism. Furthermore, the biological potential of N 1 -aryl-2-(trifluoromethyl)­benzo­[ b ]­[1,8]­naphthyridin-4­(1 H )-ones as antiparasite agents , opens the door to explore the location and distribution of the probe through fluorescence microscopy using the quenching fluorescence derived from the interaction with acid species into the target cell.…”
Section: Discussionmentioning
confidence: 99%
“…From a perspective, we think that the use of a high CT probe bearing a basic moiety in the D–A chain may also be a convenient platform for the recognition of other chemical events dependent on the acidity, such as (i) the acidity of metals (hard–soft acid–base properties), (ii) identification of halogen-bonded adducts, and (iii) recognition of a hydrogen-transfer process upon excitation, such as PCET mechanisms through selective disruption of the ICT mechanism. Furthermore, the biological potential of N 1 -aryl-2-(trifluoromethyl)­benzo­[ b ]­[1,8]­naphthyridin-4­(1 H )-ones as antiparasite agents , opens the door to explore the location and distribution of the probe through fluorescence microscopy using the quenching fluorescence derived from the interaction with acid species into the target cell.…”
Section: Discussionmentioning
confidence: 99%
“…The geometry of all tested compounds were optimized, and HOMO–LUMO orbital frontiers and EPS were obtained. Theoretical calculations were performed according to the reported strategy for similar structures . HOMO and LUMO frontier orbital maps for compounds and data are shown in Figures S6–S9 and Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical calculations were performed according to the reported strategy for similar structures. 54 HOMO and LUMO frontier orbital maps for compounds and data are shown in Figures S6–S9 and Table S2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific disruption of this photophysical mechanism can derive specific fluorescent responses that are of great applicability for the design of organic light-emitting diodes, solar energy conversion, nonlinear optical materials and fluorescent sensors. 44 Recently, we demonstrated that inserting a high-CT fluorophore featuring an internal basic moiety into a D–A chain like the N 1 -aryl-2-(trifluoromethyl)benzo[ b ][1,8]naphthyridin-4(1 H )-one 3k 45 acts as a convenient p K a probe, which shows a selective quenching response as a function of the acidity of the tested acid. 46 The chemical system was also characterized as having a remarkable dominant charge-transfer (CT) state with a relatively high stability (14.10 ns) ( 3k in Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%